Antagonistic effects of shikimic acid against focal cerebral ischemia injury in rats subjected to middle cerebral artery thrombosis. - Ma Yi; Xu Qiu-ping; Sun Jian-ning; Bai Li-min; Guo Ya-jian; Niu Jian-zhao (Acta Pharmacologica Sinica, 2016)
AIM: To study the effects of shikimic acid (SA) on focal cerebral ischemic injury after middle cerebral artery thrombosis (MCAT). METHODS: Thrombosis was induced by FeCl3 in middle cerebral artery of rats. The influences of SA on neurologic deficit (ND), infarct size (IS), brain edema, and cerebral blood flow (CBF) in ischemic region were observed. RESULTS: SA 25 and 50 mg.kg-1 i.p. for 3 d before MCAT attenuated ND, and reduced IS by 51% and 42%; and decreased brain water content from 80.7% to 79.8% and 79.9%; and increased CBF after ischemia from 50.2% of the preischemic level to 75.5% and 73.3%, respectively. In pathologic examination, there was much less thrombosis in MCA in the rat with the pretreatment by SA 25 mg.kg-1. The extent of brain ischemia was much less than that of control. CONCLUSIONS: SA reduced focal cerebral ischemic injury induced by middle cerebral artery thrombosis.